Co-production of inulinase by Kluyveromyces marxianus and Saccharomyces cerevisiae in solid state fermentation - Molefe, Nnana Mantsopa (Vaal University of Technology, 2014)
Solid-state fermentation (SFF) has emerged as a good method for the production of microbial enzymes such as inulinases. The use of low-cost agricultural plants and agro-industrial residues as substrates in SSF processes provides a value adding alternative to these otherwise under/or un-utilised vegetation. Production of inulinases, using various inulin-containing plant materials as carbon sources was studied using pure and mixed cultures of yeast strains. All substrates resulted in different levels of enzyme activity. A mixed culture of Kluyveromyces marxianus and Saccharomyces cerevisiae produced an extracellular exoinulinase when grown on different types of inulin-containing plant materials. Initial inulinase production was achieved as follows: 10 IU/gds (garlic cloves), 15 IU/gds (parsnips), 10 IU/gds (wheat bran) and 7 IU/gds (amadumbe) by K. marxianus and S. cerevisiae in a mixed culture. The production of inulinases by a mixed culture of K. marxianus and S. cerevisiae under SSF was further optimized by investigating initial moisture content, temperature, carbon source, nitrogen source, inoculum volume and inoculum ratio. The highest inulinase activity attained was in garlic cloves (85 IU/gds), followed by parsnips (65 IU/gds), wheat bran (37 IU/gds) and amadumbe (25 U/gds). The activities yielded 5.6 fold higher inulinase than in preliminary studies. The optimum pH and temperature of the crude enzyme were 5.0 and 50 oC, respectively. The pH and temperature stability of the enzyme was steady for 1 hour retaining about 64% activity. The average inulinase/invertase activity (I/S) ratio of 1.0 by crude inulinases was also observed after 48 hours. The crude extracellular enzyme extracts from the garlic cloves, parsnips, amadumbe and wheat bran were partially purified by ammonium sulphate precipitation and showed a specific activity of 9.03 U/mg, 0.08 U/mg, 4.12 U/mg and 0.133 U/mg respectively. The Km and Vmax values of the inulinase were 21.95 mM and 2.09 μM/min; 19.79 mM and 1.38 μM/min; 31.59 mM and 0.51 μM/min; and 25.74 mM and 0.23 μM/min, respectively. All extracts demonstrated potential for large-.scale production of inulinase and fructose syrup.
M. Tech. (Department of Biotechnology, Faculty of Applied and Computer Sciences), Vaal University of Technology.
Keywords: Solid-state fermentation; Microbial enzymes; Inulinases; SSF processes; Yeast strains; Fructose syrup; 572.49; Solid state fermentation.; Microbial enzymes.; Inulin.; Dissertations, Academic -- South Africa.